Penerapan Metode Simple Multi Attribut Rating Technique Dalam Merekomendasikan Lulur Terbaik Berdasarkan Minat Konsumen - Opriyani Armaya Putri; Parta Wijaya (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2020)
The purpose of this study is to recommend the best scrubs based on consumer interest with criteria such as skin type, quality, price and product size. This study uses a Decision Support System (SPK) also uses questionnaires as material to find data and share it with 150 respondents. The calculation process that the author made uses the Simple Multi Attribute Rating Technique (SMART) method. The results of this study explain that the type of scrub Shinzui brand with a value of 0.91 becomes the best scrub according to consumer interest followed by Purbasari with a value of 0.90, Herborist with a value of 0.83, Martha Tilaar with a value of 0.71 and then Vienna with a value of 0,59.